On the Number of Restrictions Determining a Periodical Sequence - G. R. Chelnokov (Моделирование и анализ информационных систем)
We consider sequences W of the period и over an alphabet consisting of l letters. It is required to determine unambiguously the sequence W picking out words which are not subwords of the sequence. For n G N we denote by Un the set of words и of length n, which are not powers (i.e. are not represented in form и = vk k > 1).